PEMODELAN KONVERSI ENERGI LISTRIK DARI CURAH HUJAN MELALUI TRANSDUSER PIEZOELEKTRIK BERBASIS ANSYS - Lumintang, Jonathan; Rantung, Jotje; Maluegha, Benny (Jurnal Poros Teknik Mesin UNSRAT, 2024)
ABSTRACT Human dependence on energy in this modern era is increasing day by day. Currently, the use of energy from non-renewable sources to meet energy needs is still quite high, namely 71%, while renewable energy is 29% (IEA, 2021). Even though the process of generating energy from non-renewable sources has a negative impact on the environment. Therefore, the utilization of renewable energy sources which are more environmentally friendly, must be maximized. To find out the energy generated from the desained model, a simulation through ANSYS is needed. In the simulation process with ANSYS, an additional program is needed to cover the characteristics of the piezoelectric and use the ACT extension, Piezo and MEMS extension. Based on the research that has been carried out, it can be concluded that for modeling rainfall with strong intensity, it is obtained that there is an electrical energy of 0,00024623 volt, a small energy conversion requires a supporting component to be used for household electrical energy. Keywords : Renewable Energy, Raindrops, Piezoelectricity, ANSYS, Simulation